Smart Card Research and Advanced Applications : 13th International Conference, CARDIS 2014, Paris, France, November 5-7, 2014. Revised Selected Papers - Joye, Marc.; Moradi, Amir.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the 13th International Conference on Smart Card Research and Advanced Applications, CARDIS 2014, held in Paris, France, in November 2014. The 15 revised full papers presented in this book were carefully reviewed and selected from 56 submissions. The papers are organized in topical sections on Java cards; software countermeasures; side-channel analysis; embedded implementations; public-key cryptography; and leakage and fault attacks.
Java cards -- Software countermeasures -- Side-channel analysis -- Embedded implementations -- Public-key cryptography -- Leakage and fault attacks.
Keywords: Data encryption (Computer science).; Computer security; Information Systems; Cryptology; Systems and Data Security; Management of Computing and Information Systems